Mapping of Mangrove Distribution in Percut Sei Tuan Sub-District Deli Serdang Regency - Delita, Fitra; Elfayetti, Elfayetti; Rohani, Rohani; Suriani, Meilinda; Ghazali Matondang, Muhammad Farouq; Herdi, Herdi (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
Mangroves are coastal ecosystems that are rich in diversity of flora and fauna. Mangroves have an important role in coastal areas in terms of ecology, biology, and economy. However, mangrove management has not balanced these three aspects and tends to be exploited for economic purposes. The purpose of this study was to map the distribution of mangroves, identify changes and zoning of mangroves in the Percut Sei Tuan subdistrict. The method used in this research is a survey method. Collecting data from Landsat Multitemporal images in 2017 and 2021 as well as field data through observation. Data analysis was performed using Envi and Arc GIS software. The results showed that the distribution of mangroves was found along the coast of Percut Sei Tuan District. The decline in mangrove ecosystems occurred in the period 2017 and 2021. Mangrove zoning in this area is in accordance with other mangrove zoning in Indonesia, which consists of open mangroves, transitional mangroves, brackish mangroves, and mangroves close to the mainland. The diversity of mangrove species in the form of true mangroves and associated mangroves was also found on the coast of Percut Sei Tuan District.